2019
DOI: 10.1007/s13300-019-0633-3
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Onset Diabetes of the Young is Not Necessarily Associated with Autosomal Inheritance: Case Description of a De Novo HFN1A Mutation

Abstract: Maturity onset diabetes of the young (MODY) accounts for up to 4% of all cases of diabetes in pediatric patients. MODY is usually characterized by autosomal dominant inheritance, impaired insulin secretion, and an average age at diagnosis of 18–26 years. Mutations in the hepatocyte nuclear factor 1-alpha (HNF1A), glucokinase, hepatocyte nuclear factor 4-alpha, and hepatocyte nuclear factor 1-beta genes are the mutations most frequently observed in cases of MODY. We herein report a case of HNF1A-MODY characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…[ 29 ] As for FHD, a powerful discriminated parameter for MODY, underestimation of self-report, de novo variants and a high proportion of FHD in T2DM, would limit its role in identifying MODY from T2DM. Furthermore, epidemiological studies have demonstrated that de novo mutations of the major MODY genes could be more frequent than what was previously assumed, [ 35 ] Stanik et al [ 36 ] described 11 de novo mutations of GCK , HNF1A , and HNF4A in 150 probands fulfilled all MODY criteria. In addition, potential biomarkers such as high-sensitivity C-reactive protein and urine C-peptide creatinine ratio have shown promising results in specifically separating the most common types of MODY from other subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] As for FHD, a powerful discriminated parameter for MODY, underestimation of self-report, de novo variants and a high proportion of FHD in T2DM, would limit its role in identifying MODY from T2DM. Furthermore, epidemiological studies have demonstrated that de novo mutations of the major MODY genes could be more frequent than what was previously assumed, [ 35 ] Stanik et al [ 36 ] described 11 de novo mutations of GCK , HNF1A , and HNF4A in 150 probands fulfilled all MODY criteria. In addition, potential biomarkers such as high-sensitivity C-reactive protein and urine C-peptide creatinine ratio have shown promising results in specifically separating the most common types of MODY from other subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…As a case of autosomal dominant inherited disease, MODY3 patients usually have a family history of diabetes ( 9 , 27 , 28 ). Some studies suggest that the probability of a family history of MODY3 is more than 20 times higher than that of T1D ( 29 ). However, some MODY patients may lack a family history of diabetes, possibly due to the following factors ( 1 ): the probability of new HNF1A-MODY mutations may be more frequent than expected, and (2) the family members of the patients were not diagnosed because of mild clinical symptoms and signs ( 29 , 30 ).…”
Section: Association Between Hnf1a Polymorphism and Mody3mentioning
confidence: 99%
“…No family history of diabetes was present. Genetic investigations revealed a de novo missense mutation in the exon 3 of HFN1A gene (HFN1A-c.709A > G) [8]. Other patterns of clinical presentation varied from hypoglycaemic episodes to hyperglycaemia.…”
Section: Hfn1a-modymentioning
confidence: 99%
“…age of onset, clinical features, type of treatment) [5]. Although the traditional criteria for MODY include a family history of diabetes, sporadic de novo mutations in a number of causative genes have been reported [6][7][8].…”
Section: Introductionmentioning
confidence: 99%